2013
DOI: 10.1002/jcla.21612
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Ves‐Matic Cube 200 For Erythrocyte Sedimentation Rate Determination

Abstract: Ves-Matic Cube 200 should be monitored carefully for good quality control. Temperature correction should be applied to study control material as recommended by the manufacturer. Ves-Matic Cube 200 device should be monitored carefully, performance studies should be performed, and the results should be checked in order to eliminate the random errors during the routine studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 10 publications
8
15
0
Order By: Relevance
“…Hemolysis caused a significant decrease in ESR levels for the Ves‐Matic Cube 200 method ( P = 0.005), though there has not been a significant difference in the measurement of ESR for the iSED method ( P = 0.766) with hemolysis. Sezer et al found that presence of lipids and hemolysis caused falsely low ESR measurements in the Ves‐Matic Cube 200 analyzer and that was in accordance with our findings.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Hemolysis caused a significant decrease in ESR levels for the Ves‐Matic Cube 200 method ( P = 0.005), though there has not been a significant difference in the measurement of ESR for the iSED method ( P = 0.766) with hemolysis. Sezer et al found that presence of lipids and hemolysis caused falsely low ESR measurements in the Ves‐Matic Cube 200 analyzer and that was in accordance with our findings.…”
Section: Discussionsupporting
confidence: 93%
“…Systematic bias for the Ves‐Matic Cube 200 was found to be higher in increscent ESR levels (mean bias of low levels = −6.2, mean bias of medium levels = 0.6, mean bias of high levels = 16.7). Sezer et al reported systemic bias as −0.7 and limits of agreement as −32.6 to 31.2; Perovic reported the bias as −0.5, limits of agreement −13.9 to 12.9 in the Ves‐Matic Cube 200 analyzer and Westergren method comparison study .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hereby, we demonstrated a much better precision of iSED with commercial control samples at both evaluated levels than in a previously published study, while patient samples yielded intrarun CVs similar to already reported data for iSED, with decreasing precision at medium and low ESR levels This is in concordance with data from a lot of validation studies of automated ESR analyzers, regardless of the analyzer type and measurement principle and can be attributed to small numbers rather than poor analytical performance, therefore not being considered clinically significant.…”
Section: Discussionsupporting
confidence: 90%